2020
DOI: 10.3390/rs12213477
|View full text |Cite
|
Sign up to set email alerts
|

Using SPOT Data and FRAGSTAS to Analyze the Relationship between Plant Diversity and Green Space Landscape Patterns in the Tropical Coastal City of Zhanjiang, China

Abstract: Urban green spaces provide a host of ecosystem services, the quantity and structure of which play an important role in human well-being. Rapid urbanization may modify urban green spaces, having various effects on plant diversity. Tropical coastal cities have urbanized rapidly in recent decades, but few studies have been conducted with a focus on their green spaces. We studied the responses of cultivated and spontaneous plants, both key components of urban flora, to the landscape structure of urban green spaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…This finding is consistent with previous studies, concluding that even areas that are highly urbanized are often dynamic in land-cover change [50,52,[81][82][83]. In addition, we found that greenspace turned out to be more fragmented, which is often considered to have a negative impact on biodiversity conservation [84][85] and the regulation of ecosystem service, such as heat mitigation [37]. However, the increased accessibility is largely benefited from the more dispersed greenspace distribution.…”
Section: Fragmented Greenspace Increased Accessibilitysupporting
confidence: 91%
“…This finding is consistent with previous studies, concluding that even areas that are highly urbanized are often dynamic in land-cover change [50,52,[81][82][83]. In addition, we found that greenspace turned out to be more fragmented, which is often considered to have a negative impact on biodiversity conservation [84][85] and the regulation of ecosystem service, such as heat mitigation [37]. However, the increased accessibility is largely benefited from the more dispersed greenspace distribution.…”
Section: Fragmented Greenspace Increased Accessibilitysupporting
confidence: 91%
“…Due to the high aesthetic quality of the urban green spaces, Zhanjiang was declared a “National Garden City” by the Chinese Ministry of Construction in 2005 [ 37 ]. In 2020, the gross domestic product (GDP) was about 6.46 trillion yuan (RMB) [ 38 ]. With rapid economic development and population growth, Zhanjiang has experienced rapid urban expansion and large areas of agricultural land have been converted to nonagricultural and urban land [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing a 30-meter spatial resolution remote sensing imagery dated June 23, 2020, sourced from Landsat 8, we implemented a supervised classification within the Environment for Visualizing Images 5.3 (ENVI 5.3; L3Harris Geospatial, Colorado, United States) to categorize Haikou's land cover into distinct classes: built-up area, herbaceous (herb) area, tree and shrub area, water area, and undeveloped land (i.e., barren or open land), achieving an overall classification accuracy of 81%. Upon completion of this process, the classified map was utilized as input for FRAGSTATS 4.2.1, adhering to the methodology delineated by Cheng and Nizamani (2020), to compute nine pattern indicators of landscape organization, which are detailed in Table 2. Subsequently, we delved into examining the impact of these indices on broader vegetational patterns of the landscape, particularly in association with spontaneous, cultivated, native, and exotic species.…”
Section: Landscape Indicesmentioning
confidence: 99%